EXPLORING THE MATTER USING NUCLEAR PHYSICS - Shobhit (Innovative Research Thoughts, 2017)
This paper provides a long-term assessment of and outlook for nuclear physics. The first phase of the paper articulates the scientific rationale and objectives of the field, while the second phase provides a global context for the field and its long-term priorities and proposes a framework for progress through 2020 and beyond.